Al-Qaeda after Awlaki - Rohan Gunaratna (2012)
The death of Anwar al-Awlaki has dealt a severe blow to al-Qaeda, its associated groups and homegrown cells. While the ongoing struggle between Islamist militancy and the United States will continue, Awlaki will be memorialised as the pioneer to exploit the cyberworld.